The answer to Line 1 is 7⋅(6−1) = 35.
The answer to Line 2 is 7⋅6−7⋅1 = 42−7 = 35.
Answer the questions below about Line 1 and Line 2 shown below.
7, dot, left bracket, 6, minus, 1, right bracket
7⋅(6−1)
Line 1
7, dot, 6, minus, 7, dot, 1
7⋅6−7⋅1
Line 2
Answer
Attempt 1 out of 3
The expression was rewritten using the .
7, dot, left bracket, 6, minus, 1, right bracket7⋅(6−1) equals 7, dot7⋅ which equals .
7, dot, 6, minus, 7, dot, 17⋅6−7⋅1 equals minus− which equals .
5 answers
can you answer this questions?
Answer the questions below about Line 1 and Line 2 shown below.
7, dot, left bracket, 6, minus, 1, right bracket
7⋅(6−1)
Line 1
7, dot, 6, minus, 7, dot, 1
7⋅6−7⋅1
Line 2
Answer
Attempt 1 out of 3
The expression was rewritten using the .
7, dot, left bracket, 6, minus, 1, right bracket7⋅(6−1) equals 7, dot7⋅ which equals .
7, dot, 6, minus, 7, dot, 17⋅6−7⋅1 equals minus− which equals .
Answer the questions below about Line 1 and Line 2 shown below.
7, dot, left bracket, 6, minus, 1, right bracket
7⋅(6−1)
Line 1
7, dot, 6, minus, 7, dot, 1
7⋅6−7⋅1
Line 2
Answer
Attempt 1 out of 3
The expression was rewritten using the .
7, dot, left bracket, 6, minus, 1, right bracket7⋅(6−1) equals 7, dot7⋅ which equals .
7, dot, 6, minus, 7, dot, 17⋅6−7⋅1 equals minus− which equals .
Certainly! Here are the answers to the questions:
Line 1:
7⋅(6−1) = 7⋅5 = 35
Line 2:
7⋅6−7⋅1 = 42−7 = 35
Line 1:
7⋅(6−1) = 7⋅5 = 35
Line 2:
7⋅6−7⋅1 = 42−7 = 35
The expression was rewritten using the
The expression was rewritten using the distributive property.